A Historiographic Analysis of Idealized Turkish House Idea - Uğur Tuztaşı (Iconarp International Journal of Architecture and Planning, 2013)
Beautiful picturesque buildings which have been a subject of protection activities come to mind first when the matter is Turkish House. However, Turkish House is not the technical name of this building culture. This concept was born as a result of historical, romantic and progressivist architecture ideal. Infact the aim of physical protection is only a minor result of this ideal. Therefore, how Turkish House is built cognitively and historical foundations of this cognitive point will be studied in this study. Sedad Hakkı Eldem’s crucial role in this matter and transmissions of researchers like Celal Esad, Süheyl Ünver Rıfat Osman prior to Eldem in conceptualizing and their relations to the topic are among the discussions from which results will be obtained. In short, this study includes discussions about the historical background of Turkish House idea which is conceptualized on the basis of a certain idealisation.